Surface modification and endothelialization of polyurethane for vascular tissue engineering applications: a review. (12th December 2016) - Adipurnama, Iman; Yang, Ming-Chien; Ciach, Tomasz; Butruk-Raszeja, Beata
Abstract : This review summarizes the surface modification and endothelialization of polyurethane for vascular tissue engineering applications, including recent developments and strategies. Abstract : Cardiovascular implants, especially vascular grafts made of synthetic polymers, find wide clinical applications in the treatment of cardiovascular diseases. However, cases of failure still exist, notably caused by restenosis and thrombus formation. Aiming to solve these problems, various approaches to surface modification of synthetic vascular grafts have been used to improve both the hemocompatibility and long-term patency of artificial vascular grafts. Surface modification using hydrophilic molecules can enhance hemocompatibility, but this may limit the initial vascular endothelial cell adhesion. Therefore, the improvement of endothelialization on these grafts with specific peptides and biomolecules is now an exciting field of research. In this review, several techniques to improve surface modification and endothelialization on vascular grafts, mainly polyurethane (PU) grafts, are summarized, together with the recent development and evolution of the different strategies: from the use of PEG, zwitterions, and polysaccharides to peptides and other biomolecules and genes; from in vitro endothelialization to in vivo endothelialization; and from bio-inert and bio-active to bio-mimetic approaches.